Evaluation of mortality risk and surgical outcomes based on Charlson comorbidity index in emergency hernia repair patients - Mustafa Karaagac; Sedat Carkit (International Journal of Abdominal Wall and Hernia Surgery)
CONTEXT: Hernias are common surgical conditions that may require emergency interventions due to complications such as strangulation, bowel obstruction, or ischemia. These situations significantly impact clinical outcomes and necessitate robust risk assessment tools. AIMS: To evaluate mortality risk and surgical outcomes in emergency hernia repair patients using the Charlson comorbidity index (CCI) and to optimize clinical decision-making processes. SETTINGS AND DESIGN: A retrospective study conducted at our General Surgery Clinic from 2021 to 2023. MATERIALS AND METHODS: Data from 159 patients undergoing emergency hernia surgery were retrospectively analyzed. Variables included demographic data, hernia types, surgical interventions, and clinical outcomes. CCI and American Society of Anesthesiologists scores were calculated, and their impacts on mortality were assessed using logistic regression and chi-square tests. STATISTICAL ANALYSIS USED: Logistic regression, chi-square tests, and cross-tabulation analyses. RESULTS: Patients with a CCI score of 3–4 showed a significantly higher mortality risk (P = 0.000), while those with scores ≥5 exhibited elevated but statistically insignificant mortality risks (P = 0.141). Mortality was significantly associated with intestinal resection (P = 0.001). The time of presentation correlated with the likelihood of requiring resection (P = 0.000). CONCLUSION: CCI is a reliable predictor of mortality risk in emergency hernia repair patients. Early risk assessment and timely intervention are crucial for improving outcomes.